PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE)MATERI PERCAKAPAN KELAS V SD NEGERI 104273 CILAWAN KECAMATAN PANTAI CERMIN T.P 2017-2018 - RAJAGUKGUK, WAHYU SRI REJEKI (Unversitas Katolik Santo Thomas, 2018)
This study aims to: (1) to improve student learning outcomes in Indonesian language lesson using cooperative model model of TPS (Think Pair Share) class V SD Negeri 104273 Cilawan Kecamatan Pantai Cermin T.P 2017-2018. To find out how the implementation of learning by using cooperative cooperative learning model of TPS type (Think Pair Share) on Indonesian lesson in class V SD Negeri 104273 Cilawan T.P 2017-2018. Subjects in carrying out the action in this study are researchers who work together with the homeroom as an observer, while the object in this study is the students of grade V SD Negeri 104273 Cilawan which amounted to 33 students consisting of 15 men and 18 women. Data collection techniques through observation of the results of learning tests and student learning activities. The results of this study showed an increase in student learning outcomes on the subjects of Bahasa Indonesia class V conversational materials SD Negeri 104273 Cilawan. This is evident from the results of research conducted on the pretest of students who got the complete value of 7 students or 21.21% while the students who did not complete as many as 26 people or 78.79. Then continued the research on the first cycle of students who got the complete value of 14 students or 42.42% while students who do not complete as many as 19 students or 57.58%, then there is an increase in the cycle I compared to the pretest. However, it has not met the completeness category that has been specified. Then proceeded on the second cycle of students who received a complete score of 28 students or 84, 85% while students who are not complete as many as 5 students or 15.15%, then there is an increase in cycle II compared to cycle I and has fulfilled the mastery already specified. Furthermore, teacher activity in observation cycle I obtained an average of 60% and in cycle II increased to 84%. While the student activity on the learning process memeproleh average of 64% and on the second cycle has increased 88%. Thus, it is concluded that by using cooperative learning model of TPS type (Think Pair Share) on Indonesian Language conversation material in class V SD Negeri 104273 Cilawan can improve student learning outcomes. Therefore it is suggested for the next learning to use cooperative model of TPS type (Think Pair Share) so that student learning result can be increased.